Molecular-based diagnostics, including future trends. (October 2021) - Goldenberg, Simon; Merrick, Blair
Abstract: Microbiological diagnosis has traditionally relied on phenotypic methods involving culture and biochemical testing to identify and characterize clinically significant pathogens. The utility of these techniques can be limited by poor sensitivity and long turn-around time. Molecular and mass spectrometry techniques have rapidly changed the diagnostic landscape and the management of patients with infections. Compared with conventional culture-based techniques, these modern approaches can rapidly provide more specific information on organism identity and the presence of resistance mechanisms. These methods are expected to contribute substantially to enhancing antimicrobial stewardship and to decreasing 'time to appropriate antibiotics', one of the most important factors in improving the prognosis of patients with life-threatening infections. The UK government review on antimicrobial resistance has clearly laid out the real implications of spreading drug resistance, and provides an overview of how rapid diagnostics can play an important role in reducing unnecessary antimicrobial use and/or allowing early antibiotic de-escalation. This article gives an overview of some of the practical applications of these modern technologies.